FEATURES OF HOTEL MANAGEMENT - Abduganiyev Abdulaziz Abdugofur ugli (Western European Studies, 2024)
Hotel management is a complex and challenging field that requires various skills and competencies to effectively manage a hotel property. This article provides an overview of the key features of hotel management, including reservation management, guest services, revenue management, housekeeping, food and beverage operations, marketing and sales, and human resource management. By focusing on these important aspects of hotel management, hoteliers can improve operational efficiency, improve customer satisfaction, and increase profitability.
Keywords: hotel; hoteltravel agencies; business